Recuperación de cartera vencida y su incidencia en la rentabilidad de la comercializadora ile, cantón Quevedo, año 2022. - Cárdenas Dávila, Génesis Gabriela (2024)
The study carried out in 2022 on the recovery of past-due portfolio and its impact on the profitability of Comercializadora ILE aimed to deepen the analysis of the management of past-due portfolio and its direct influence on profitability. To achieve this, descriptive, documentary and field research was used, applying deductive, inductive and analytical methods. Interviews were carried out with the sales supervisor, the administrator and the salespeople, and the main findings reflected factors such as lack of communication, credit accumulation and poor implementation of credit policies, generating important concerns. In addition, a survey was conducted aimed at the Marketing Company's clients, using a bank of questions based on the Likert scale. The company faced significant challenges in managing its overdue portfolio, evidencing the presence of outstanding accounts that required detailed analysis to understand the factors that contributed to their accumulation and to strengthen the company's economic stability.